1975
DOI: 10.1037/h0076369
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the MMPI Pd scale among black males.

Abstract: The validity of the Minnesota Multiphasic Personality Inventory/Psychopathic Deviate (Pd) and Pd + ,4K scales to discriminate levels of social deviance among young black men was investigated. Study 1 established that black inmates at a federal correctional institution had significantly higher scores on both scales than culturally deprived black university students. Study 2 demonstrated that among the inmates, recidivists had significantly higher scores than first offenders and that among the students, there we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…McCreary and Padilla (1977) found that misdemeanor black offenders had lower K and H Y scores and higher MA scores than did white misdemeanor offenders, with the two groups matched on educational level and occupation, but not intelligence. Elion and Megargee (1975) found that black prisoners had higher PD scores than black deprived college students, that black recidivists had higher PD scores than black first offenders, and that black prisoners had higher PD scores than white prisoners. Rosenblatt and Pritchard (1978) found that the effects of IQ interacted with racial effects, and differences between black and white offenders were found only in the low IQ groups.…”
Section: Racial Differencesmentioning
confidence: 97%
“…McCreary and Padilla (1977) found that misdemeanor black offenders had lower K and H Y scores and higher MA scores than did white misdemeanor offenders, with the two groups matched on educational level and occupation, but not intelligence. Elion and Megargee (1975) found that black prisoners had higher PD scores than black deprived college students, that black recidivists had higher PD scores than black first offenders, and that black prisoners had higher PD scores than white prisoners. Rosenblatt and Pritchard (1978) found that the effects of IQ interacted with racial effects, and differences between black and white offenders were found only in the low IQ groups.…”
Section: Racial Differencesmentioning
confidence: 97%
“…As part of a larger study, Costello, Fine, and Blau (1973;1) found no significant differences between their samples of black and white inmates. Elion and Megargee (1975;3) investigated the validity of the Pd scale among black males using groups of prisoners and groups of college students. They found that black inmates scored significantly higher on the Pd scale than both a group of "culturally deprived black male university students" and a group of white inmates.…”
Section: Mmpi Differences Across Race and Sexmentioning
confidence: 99%
“…Using an additional 283 subjects from delinquent populations, it was demonstrated that the composite was an excellent discriminator between delinquent and general populations of males and females even when intelligence and social status were controlled.Elevation of the T scores on both Scales 4 and 9 of the Minnesota Multiphasic Personality Inventory (MMPI) has been thought to form the profile characteristic of the male juvenile delinquent (Dahlstrom & Welsh, 1960;Dahlstrom, Welsh, & Dahlstrom, 1972;Hathaway & Monachesi, 1953). Scale 4 (Psychopathic Deviate) by itself has been used to measure levels of social deviance or antisocial behavior (Elion & Megargee, 1975;Hathaway & Monachesi, 1953; Megargee & Mendelsohn, 1962). Dahlstrom et al (1972) noted that marked elevations on Scale 4 can be observed in prison groups.…”
mentioning
confidence: 99%